2010
DOI: 10.17705/1cais.02720
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Uses and Gratifications for Using Computer-Mediated Communication Media in Learning Contexts

Abstract: Despite a growing stream of research into the use of computer-mediated communication (CMC) media in higher education, there remains limited understanding about the students' motivations for using CMC alongside non-CMC media within a learning context. This article identifies seven dimensions of motivation from the perspective of uses and gratifications (U&G), including information seeking, convenience, connectivity, problem solving, content management, social presence, and social context cues. It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 147 publications
(167 reference statements)
4
22
0
Order By: Relevance
“…''), we concluded that Hypothesis 2 was partially supported. This is consistent with other research, in that the motivation to consume content for learning purposes is more influential on outcomes than mere media exposure (e.g., Guo, Tan, & Cheung, 2010). For example, Tiggemann (2005) found that viewing television with a motivation of social learning was a stronger predictor of reported body image concern among adolescents than was sheer amount of television exposure.…”
Section: Discussionsupporting
confidence: 90%
“…''), we concluded that Hypothesis 2 was partially supported. This is consistent with other research, in that the motivation to consume content for learning purposes is more influential on outcomes than mere media exposure (e.g., Guo, Tan, & Cheung, 2010). For example, Tiggemann (2005) found that viewing television with a motivation of social learning was a stronger predictor of reported body image concern among adolescents than was sheer amount of television exposure.…”
Section: Discussionsupporting
confidence: 90%
“…From the findings, adult learners are most likely to adopt m‐learning if the medium is able to support their interaction needs. Being a student and also working at the same time required them to expand connectivity, which allows them to connect and collaborate with other students (Guo et al , ). Besides that, adult learners' decision to adopt m‐learning is also strongly influenced by the ability of the medium to allow them to achieve personal fulfillment and a pleasant experience when using the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this theoretical lens, students' motivation to use a medium can be categorized into three main categories: (1) cognitive need, (2) social need and (3) affective need. Empirical evidence shows that these attributes can generally be applied to any media usage, including media technologies used in online learning context (Guo, Zhang & Stevens, ; Guo et al , ; Mondi et al , ). For instance, to fulfill cognitive needs, the tool (ie, m‐learning application) should be able to motivate adult learners to seek information—knowledge that is related to the course.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations